Class, ethnicity, gender and Latino entrepreneurship [electronic resource] - Verdaguer, Maraia Eugenia (New approaches in sociology, 2009)
Verdaguer examines first-generation Latino entrepreneurs, revealing not only that Latinos' strategies for access to business ownership and development are cut across class, ethnic and gender lines, but also that immigrants' options and practices remain shaped by patriarchal gender relations within the immigrant family, community and economy.